Science Teacher’s Perception of Digital Technology-Based Learning in the 21st Century - Roza, Media; Lufri, Lufri; Andromeda, Andromeda; Mufit, Fatni (FKIP Universitas Lampung, 2022)
Science Teacher's Perception of Digital Technology-Based Learning in the 21st Century. Objective: The research aims to identify science teachers' perceptions of digital technology-based learning in the 21st century. Method: This type of research is survey research. Perception data was collected through questionnaires and interviews of 30 science teachers in West Sumatra. Data analysis uses descriptive analysis. Findings: It was found that the main components determining the success of digital technology-based science learning are competence, effort, and teacher commitment. Teachers are greatly helped to prepare learning plans, choose teaching materials and media, carry out learning, and evaluate with digital technology. This affects the student's learning process and outcomes. Students feel interested, excited, and enthusiastic. Conclusion: 21st-century skills can be trained through learning based on digital technology. These findings can serve as a basis in determining the models and media of science learning based on digital technology in the 21st century.Keywords: perception, digital technology, 21st-century skills.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202222